Arterial Blood Gas Parameters to Evaluate Oxygenation and Acid-Base Disorders in Corticosteroid-Receiving Severe and Critical COVID-19 Patients - Temenggung, Bintang; Setiawan, Herley Windo; Rochmanti, Maftuchah; Rosyid, Alfian Nur (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2024)
Highlights: Both severe and critical COVID-19 patients primarily presented with hypoxemia. Severe and critical COVID-19 patients differed through their tendencies towards respiratory alkalosis/metabolic acidosis and respiratory acidosis, respectively.   Abstract Introduction: Increased inflammation and immune dysregulation in severe and critical COVID-19 trigger oxygen and acid-base disorders, possibly mitigated by corticosteroids. Variations in arterial blood gas (ABG) parameters and the influence of corticosteroid administration have become a concern for clinicians. This study aimed to uncover significant differences in temporal arterial blood gas parameters between severe and critical COVID-19 cases undergoing corticosteroid treatment. Methods: This case-control study, which adhered to the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines, analyzed severe (n=27) and critical (n=41) COVID-19 patients treated in the high care unit (HCU) and the intensive care unit (ICU) of Universitas Airlangga Hospital, Surabaya, from May to July 2021. Arterial blood gas results were categorized into three evaluations (E1-E3) based on collection days. The International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) for Macintosh version 27.0 was used for statistical analysis, with a p<0.05 considered statistically significant. Results: Hypoxemia through PaO2 and P/F ratios was prominent in both groups throughout E1-E3, with differences only in E1 P/F ratios (p=0.003). While SaO2 stayed normal in severe cases, critical cases were low, with differences in E1 (p=0.012) and E3 (p=0.004). Severe cases maintained normal pH, while critical cases tended towards acidemia, notably differing in E1-E3. Both groups had low HCO3 levels, differing only in E2 (p<0.001). Severe and critical groups exhibited low and high PaCO2 trends, respectively, with distinctions in E2 (p<0.001) and E3 (p=0.003). Conclusion: Hypoxemia was prevalent in both groups. Compensated respiratory alkalosis or metabolic acidosis was common in the severe group, while the critical presented with respiratory acidosis.